Alternatif Penanganan Stabilitas Timbunan dan Lereng pada Oprit Jembatan dengan Mortar Busa (Studi Kasus : JU Rel KA Cibitung – Cilincing) - Annissa Yoga Prastika; Wahyu Febriyanto; Dewi Indriyana; Bagas Wahyu Adhi; Fatchur Roehman; Faqih, Nasyiin (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Soft soil is caused by cohesion, a low internal friction angle and high compressibility. If not recognized and investigated it can cause instability and long-term decline that cannot be tolerated. One of the treatments that occurs in soft soil is light backfilling with foam mortar. The aim of this research is to carry out an analysis of the stability of embankments using lightweight materials at the location of bridge embankments in order to predict how much of an impact there will be in reducing settlement and increasing embankment stability. Analysis was carried out using the Finite Element Method with the help of the Plaxis 2D program. The method used in this research is descriptive qualitative, namely research by collecting primary and secondary data from the parameters and variables studied and then analyzing them to draw conclusions. In the results of the analysis using Plaxis Softwere using foam mortar treatment with an embankment slope of 1: 1.5, the results showed that the decline in 1 year was 4 cm (meeting the design criteria), the decline in 10 years was 2.8 cm (meeting the design criteria), apart from that the safety factor using foam mortar was also greater than the design criteria, which means the stability of the slope is safe.